Muséologie et Autochtones du Québec et du Canada - Julie BIBAUD (Cahiers du MIMMOC)
Museums contribution to the European colonial project was and is still criticized. In the context of Indigenous movements of the 1960s, various strategies have been put forward to regain control over of their own culture representation including objects and human remains repatriation and the creation of cultural institutions. This movement also questions the rationality of Western museology and advocate for its decolonization. This aspect is the subject of the present article. Through the analysis of Indigenous museum professional narratives of practices, we will try to understand the original way in which these actors express a museum practice corresponding to their values.